Peningkatan Pengetahuan tentang Hipertensi pada Ibu Rumah - Tedy Candra Lesmana; Novita Sekarwati (STIKES Wira Husada Yogyakarta, 2022)
Increased knowledge about hypertension in housewives. One of the causes of the high incidence of high hypertension in rural areas is because there are still many people who do not know that they suffer from hypertension. Women who are at risk of developing hypertension need to be given knowledge through education to prevent it. The purpose of community service activities is to increase public knowledge about hypertension. The method used in community service activities is in the form of counseling. The target of the activity is the housewives of Dusun Sindon. The counseling material contains the understanding and prevention of hypertension in the form of Powerpoint slides. The material is delivered using a laptop and LCD. During the delivery of the material accompanied by discussions with participants. Measurement of the level of change in knowledge about hypertension using pre-test and post-test questionnaires filled out by mothers before and after the provision of counseling materials. Efforts to change people's behavior to prevent hypertension by making posters. The activity was attended by 12 housewives. The results of the evaluation showed that there was an increase in the number of housewives in the good category. Placing posters and practicing antihypertensive exercise were carried out to change their behavior. The results of service activities can increase knowledge about hypertension in housewives and are able to do antihypertensive exercise well..